PERAN KATEKIS VOLUNTEER MENURUT DEKRIT APOSTOLICAM ACTUOCITATEM ARTIKEL 6 DALAM HIDUP MENGGEREJA ORANG MUDA KATOLIK DI PAROKI SANTO FRANSISKUS ASISI MAMSENA - Ukat, Kristophorus; Funan, Raineldis (Sekolah Tinggi Pastoral St. Petrus Keuskupan Atambua, 2024)
Volunteer catechists are people who voluntarily become proclaimers of God's word, people who are very concerned about the development of the Church. On the basis of that call, all members of God's people have the right and obligation to participate in the duties of the Church. The focus of this research is on volunteer catechists, especially in the Church's five duties, namely Koinonia or living in fellowship, Liturgya or living in prayer/worship, Diakonia or living in service, Kerygma or living to preach, Martirya or living to give testimony. This study uses a qualitative descriptive design with a field study design, by obtaining data through observation, interviews and documentation. The findings show that in St. Francis of Assisi Mamsena Parish, there is a shortage of catechist workers who hinder the development of the Church through various existing activities, such as choir training, worship in the ward, SEKAMI activities, faith building and so on. So OMK is not interested and has no awareness of his duties as a member of the Church. Thus, volunteer catechists answer existing problems with all their abilities and knowledge such as being able to train choirs, lead worship without priests, build faith with SEKAMI children, make pilgrimages with OMK, become movers in the environment, coordinators in several activities in the Church. So that OMK can emulate and emulate volunteer catechists as members of the Church who are able to carry out the Church's pancatask.